KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN KEHUTANAN PASCA UNDANG-UNDANG CIPTA KERJA [The Authority of Local Governments in the Context of Forestry Management after the Law on Job Creation] - Hario Danang Pambudhi; Muhammad Arief Virgy (Law Review, 2022)
The Indonesian government initiated a law called Job Creation which aims to facilitate the flow of licensing bureaucracy to increase investment in Indonesia. However, there are problems that have come to the attention of the author regarding the regulation of forestry matters in this regulation, namely the centralization of authority to issue permits in the central government, the role of local governments in the formation and assessment of environmental impact analysis (AMDAL) and Environmental Management Efforts-Environmental Monitoring Efforts (UKL-UPL), and regarding the features of the National Strategic Project (PSN). These problems are the main discussion of the authors in this study. By using normative juridical research through a statutory approach as well as descriptive analytical concepts, the authors conclude that forestry regulations in these laws tend to restore the dignity of centralization of authority in the context of forest management authority, particularly with regard to forest use. This is not in line with the constitutional design regulated in the constitution regarding the division of authority for forest use between the central and regional governments which must be carried out based on the spirit of autonomy as wide as possible in a fair and harmonious manner.Bahasa Indonesia Abstrak: Pemerintah Indonesia menginisiasi sebuah Undang-Undang dengan nama Cipta Kerja yang bertujuan untuk mempermudah alur birokrasi perizinan untuk meningkatkan investasi di Indonesia. Namun, terdapat permasalahan yang menjadi perhatian penulis terkait pengaturan soal kehutanan dalam regulasi ini, yaitu pemusatan kewenangan pemberian izin di pemerintah pusat, peran pemerintah daerah dalam pembentukan dan penilaian analisis mengenai dampak lingkungan (AMDAL) dan Upaya Pengelolaan Lingkungan Hidup-Upaya Pemantauan Lingkungan Hidup (UKL-UPL), dan perihal keistimewaan Proyek Strategis Nasional (PSN). Permasalahan tersebut menjadi bahasan utama penulis pada penelitian ini. Dengan menggunakan penelitian yuridis normatif melalui pendekatan perundang-undangan serta konsep yang bersifat deskriptif analitis, penulis berkesimpulan bahwa pengaturan kehutanan dalam undang-undang tersebut cenderung mengembalikan marwah sentralisasi kewenangan dalam konteks kewenangan pengelolaan hutan, khususnya berkaitan dengan pemanfaatan hutan. Hal ini tidak selaras dengan desain konstitusional yang diatur dalam konstitusi mengenai pembagian kewenangan pemanfaatan hutan antara pemerintah pusat dan daerah yang harus diselenggarakan berdasarkan semangat otonomi seluas-luasnya yang adil dan selaras.